Legal Protection for Patients in Settlement of Medical Disputes through the Courts (Case Study of South Jakarta District Court Decision Number 538 / Pdt.G / 2016 / PN. Jkt. Cell) - Rezka Zahra Humaira; I. Edward Kurnia; Valentinus Suroto (Universitas Katolik Soegijapranata Semarang, 2020)
One of in court mediation failure cases was the case of the South Jakarta District Court Nr.538/Pdt.G/2016/PN. Jkt. Sel. The objective of this study was to determine judges’ legal considerations in making decisions relating to the South Jakarta District Court case and to know the legal protection to the patient in resolving the medical disputes which were conducted through the court.This study used a legal-normative approach having descriptive-analytical specifications. The data used were primary and secondary meanwhile the data gathering techniques were by interviews and library studies. The interviews were conducted with informants, namely one judge of South Jakarta State Court, two judges of Semarang District Court, one Deputy Civil Registrar of the Supreme Court, and deputy chairman of MKEK. The library studies were conducted by studying primary secondary, and tertiary legal materials beside some other relevant written materials.The results of this study showed that the plaintiff, in this case, was the patient, was not legally protected when having a medical dispute case in the court. It was because the judge was not right in making a judgment. The plaintiff filed a lawsuit directly to the court to be able to resolve the case of facelift operation alleged malpractice. However, the plaintiff's claim was not accepted because according to the judges a medical dispute between doctors and patients should be done through Medical Ethics Commission Assembly (MKEK) first. This consideration is based on the Circular Letter of Supreme Court (SEMA) 1982 (without numbers) and expert opinion. However, if it used an analogy of MKEK which was treated equally to MKDKI, the submission of a medical dispute claim did not require to be processed through MKEK first. One of the reasons for the judge's irrelevance in the decision was the fact that SEMA used as the basis of the judge’s decision could not be found, even after being confirmed at the Supreme Court's Law and Public Relations Bureau. Besides, there had been many legislations that could be used as considerations of the decision such as Act Nr. 36 of 2009, the Act Nr. 29 of 2004, and the Act Nr. 44 of 2009.